Rainwater harvesting in arid and semi-arid lands of Africa: challenges and opportunities - Etienne Umukiza; Romain Ntole; Sylvester R. Chikavumbwa; Erion Bwambale; Davis Sibale; Zechariah Jeremaih; Ciro Apollonio; Andrea Petroselli (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: Arid and semi-arid lands often face a shortage of freshwater due to uncontrolled runoff. In arid and semi-arid regions of Africa, rainwater harvesting is a promising solution that can be implemented for multiple purposes such as agriculture, recreation, flood control, and availability of drinking water. The present review aims to highlight the benefits, opportunities and challenges associated with rainwater harvesting in arid and semi-arid lands of Africa.